Non-interventional study of the epidemiological and clinical aspects of war-related spinal cord injuries among military personnel - Artemenko, V.O.; Matsipura , M.M.; Sazonova, S.O. (Medicni Perspektivi, 2025)
With the beginning of active hostilities in Ukraine the amount of victims with gunshot, mine-explosive and shrapnel injuries of the musculoskeletal system among military personnel increased sharply. Therefore, the problems of treatment and rehabilitation of victims of hostilities have become especially acute in the last year. The purpose of the study was to characterize combat spinal cord injuries in military personnel based on the analyzed literature and clinical observations based on medical institutions. Primary literature search was conducted using Medline, Excerpta Medica dataBASE, and PsycINFO databases published from 2014 to 2024. After STROBE screening of articles, reviewers abstracted relevant data for analysis and statistical processing using Microsoft Excel Atte Stat 2010. In total, 263 publications were analyzed, of which 25 articles met the inclusion and exclusion criteria, and only 7 articles altogether created a homogeneous sample in terms of age, gender, time since the injury was sustained. Data from the neurological status of the patients’ medical histories, including the Spinal Cord Independence Scale, were used to construct recovery profiles for the first year after injury. For analysis, 50 case histories were randomly selected from the paraplegic cohort, and 50 from the tetraplegic cohort. Both groups were homogeneous according to all criteria. The total number of analyzed medical histories was n=100. To create recovery profiles, data on the neurological status of the patients, including the spinal cord independence scale, were taken. The gunshot traumas of the musculoskeletal system are accompanied by plenty of complications and unsatisfactory by the anatomic and functional results of treatment. Such injuries are characterized by a traumatic disease that develops in response to combat trauma and has a long and complicated course, high rates of mortality and severe disability. Damage to the spine and spinal cord is characterized by high mortality (19.1-52.9%) and permanent disability. The most common mechanisms of spinal cord injuries (SCI) were gunshot (from 9.4 to 93.3%), explosive (from 2.7% to 81.8%). Gunshot SCI most often affected the cervical (from 25 to 88% according to various studies) and thoracic part of spinal cord (24-63%). Blast SCI more often affected the lower parts of spine: lumbar – from 21 to 72%, sacral – from 27 to 89%. The share of complete injuries (18.2-90%) was greater than the share of incomplete SCI (10-81.8%). Level and severity of SCI matter in neurological recovery, with the least favorable prognosis among patients with tetraplegia with complete SCI (type A) and the most favorable prognosis – among patients with paraplegia with type D. Only 30.2% of patients with type A SCI progressed to type B (17.3%), type C (5.8%) or type D (7.2%) within a year after trauma, while 76.7% of patients with type B or type C SCI improved their clinical grade and only 8.5% patients with type D were switched to type E. In the context of the genesis of combat SCI, the largest share is occupied by explosive and mine-explosive injuries, which most often affect the sacral and lumbar spine according to the mechanism of injury, as well as gunshot wounds, which more often affect the cervical and thoracic regions, and determines the ranking of the clinical picture among patients. Differences in the level and severity of injury have obvious consequences in terms of neurological and functional recovery in the whole spectrum, with the least favorable prognosis among patients with tetraplegia with complete injury (type A) and the most favorable prognosis among patients with paraplegia with type D injury, according to the international standard for neurological classification of spinal cord injury.